Determination of Supply Chain Performance and Market Performance: Impact of Supply Chain Activities in Indonesian Crude Palm Oil Industry - Roespinoedji, Djoko; Violina, Sriyani; Mardiansyah, Viddi; Setijadi, Setijadi; Isa, Azizan Mohamed (International Journal of Supply Chain Management, 2019)
Supply chain practices are crucial in determining the performance of firms. The current study investigates impact of supply chain practices for determining the market and supply chain performance in crude palm oil industry of Indonesia. The supply chain activities were taken from previous literature including supplier relationship, customer relationships and waste reduction. The objective of the study was to determine the impact of these crucial supply chain activities on market performance and supply chain performance in Indonesian crude palm oil producers. Data was collected from palm oil producers in Jakarta Indonesia, response rate was observed as 77%. The data was analyzed by using AMOS SEM technique. The relationship was examined between constructs and found mixed results, study revealed few practices has significantly associated with market performance and supply chain performance and did not find any significant influence between supplier relation and market performance; waste reduction and market performance was rejected statistically.